Traduire l'ironie - Lievois, Katrien; Schoentjes, Pierre (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Irony is a salient feature of common discourse and of some of contemporary art ’s more sophisticated representations. An intriguing characteristic of art and speech, irony ’s power and relevance reaches well beyond the enclaves of academic research and reflection. Translating irony involves a series of interpretative gestures which are not solely provoked by or confined to the act of translation as such. Even when one does not move between languages, reading irony always involves an act of interpretation which ‘translates’ a meaning out of a text that is not ‘given’. This article offers a critical survey of the literature on the translation of irony while aiming to monitor and explain the techniques and challenges involved in its translation.